Peningkatan Hasil Belajar Mekanika Teknik Menggunakan Model Pembelajaran STAD (Student Teams Achievement Division) pada Siswa Kelas X DPIB2 SMKN 2 Karang Baru Kabupaten Aceh Tamiang - Ida Khairani (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
Improving Engineering Mechanics Learning Outcomes Using the STAD (Student Teams Achievement Division) Learning Model for Class X DPIB2 Students at SMK Negeri 2 Karang Baru Aceh Tamiang. The goal to be achieved in this Classroom Action Research (CAR) is for students to increase their interest in learning Engineering Mechanics, so that students gain knowledge, skills and positive attitude changes. This Classroom Action Research (CAR) was conducted in class X DPIB2 SMK Negeri 2 Karang Baru, located on Jalan Ir. H Juanda Karang Baru, Karang Baru, Aceh Tamiang Aceh Province The number of students is 22 people, with heterogeneous socio-economic backgrounds. Implementation of Classroom Action Research carried out in 2 cycles. In the first cycle, they could not achieve the expected results, because students were still not used to it. After there is motivation, in the implementation of the second cycle there is a very significant change in a good direction. Students are already showing an increased interest in studying Engineering Mechanics. STAD type cooperative learning can change learning from teacher center focus to student centered. The results showed that there was an increase in the activeness of student learning as indicated by an increase in the average class score from cycle I to cycle II of 16.84%, and an increase in student learning outcomes as indicated by an increase in the average class score, namely from the pre-cycle to cycle I of 8.28% and from cycle I to cycle II of 10.40%.